The International Conference on Technologies and Materials for Renewable Energy, Environment and Sustainability. (August 2015) - Salame, Chafic; Aillerie, Michel; Papageorgas, Panagiotis
Abstract: The International Conference on Technologies and Materials for Renewable Energy, Environment and Sustainability is an annual event organized by the Euro-Mediterranean Institute for Sustainable Development (EUMISD.org). TMREES15, held in April 17-20, 2014 in Beirut - Lebanon, has a main objective to promote sustainable, healthy and diverse ecosystems; encourage and support the international energy security systems through development of green based and other renewable resources and processes, bringing together participants from international research centers, universities, industry and administrative organizations around the world to exchange innovative and novel ideas, explore enabling technologies, share field trial experiences in sustainability issues and to open a new window on the circumstances of the classical energy sources and their harmful impact on people, society and environment. The TMREES15 international conference has a general philosophy to gather the global research community, discuss, present and to network the latest developments and innovations in sustainability.